2014
DOI: 10.1111/bcp.12335
|View full text |Cite
|
Sign up to set email alerts
|

Increased platelet expression of glycoprotein IIIa following aspirin treatment in aspirin‐resistant but not aspirin‐sensitive subjects

Abstract: Aims Aspirin is widely used as an anti‐platelet agent for cardiovascular prophylaxis. Despite aspirin treatment, many patients experience recurrent thrombotic events, and aspirin resistance may contribute to this. We examined the prevalence of aspirin resistance in a healthy population, and investigated whether the platelet proteome differed in aspirin‐resistant subjects. Methods Ninety‐three healthy subjects received aspirin 300 mg daily for 28 days. Before and at the end of treatment, urine was taken to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…Floyd et al. has demonstrated that glycoprotein IIIa (A isoform) expression has been increased in lysed platelets . Besides, a significant increase in the acetylation rate and a significant decrease in glycation have been reported by Finamore et al.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Floyd et al. has demonstrated that glycoprotein IIIa (A isoform) expression has been increased in lysed platelets . Besides, a significant increase in the acetylation rate and a significant decrease in glycation have been reported by Finamore et al.…”
Section: Introductionmentioning
confidence: 84%
“…Two of the most widely used antiplatelet therapies include aspirin (ASA) and clopidogrel (CLOP). ASA irreversibly inhibits the platelets from producing thromboxane A 2 through acetylation of the cyclo‐oxygenase‐1 enzyme at Ser‐529 residue while CLOP acts by binding specifically and irreversibly to the platelet P2RY12 purinergic receptor, inhibiting ADP‐mediated platelet activation and aggregation . Numerous studies assessing the impact of antiplatelet agents on TBI have been proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRP4 might also reduce cytosolic concentrations of cAMP e cGMP as it functions as a negative regulator that in turn limits the effect of platelet cyclic nucleotides [24]. It is possible that chronic NSAIDs treatment may determine up-regulation of other proteins as well as MRP4, parallel to what has been seen after chronic aspirin treatment [25,26]. This study has excluded that platelet hyper-reactivity could depend on an increased TxB2 release as we demonstrated that arachidonic acid induced TxB2 production is the same in OA patients, with high levels of MRP4, and in the control population.…”
Section: Discussionmentioning
confidence: 99%
“…This finding offers new clues to the mechanism of aspirin resistance, and also suggests that platelet GPIIIa receptor may become a novel biomarker for aspirin resistance. [13] In another study, aspirin resistance was found to correlate with age, and the incidence of aspirin resistance was high in patients with coronary heart disease (CHD) aged 75 years or above. [14] It was also shown that enteric-coated aspirin may cause aspirin resistance, and therefore low-dose enteric-coated aspirin as a medication for secondary prevention of cardiovascular diseases may not achieve complete inhibition of platelet COX due to inadequate bioavailability.…”
Section: Dosagementioning
confidence: 99%